Corona Pandemic, Foreign Terminology, and Society Symbolic Interaction Seen through Memes - Nurvita Wijayanti; Panggio Restu Wilujeng (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2021)
The Indonesian government policy to prevent the spread of Covid-19 has been interpreted in many ways by its society. One of the reasons is the use of English terminology when issuing the regulation. As a consequence, there are the appearance of lots of funny memes showing how society understands the government policy. Therefore, this study aims to analyze the foreign terminology used by the government followed by English terminology that was spread that was spread addressed to Indonesian who cannot speak English in major. This study uses descriptive qualitative method; as and the main data are the memes found in social media. These memes are analyzed linguistically using phono-orthography perspective to know about the cognitive acquirement of people in Indonesia. The next step is by having a sociological perspective using by having sociological perspective using symbolic interaction theory to acknowledge the social interpretation of the English terminology.